The impact of EndoBarrier gastrointestinal liner in obese patients with normal glucose tolerance and in patients with type 2 diabetes. Issue 2 (14th November 2016) - Rohde, Ulrich; Federspiel, Cecilie A.; Vilmann, Peter; Langholz, Ebbe; Friis, Steffen U.; Krakauer, Martin; Rehfeld, Jens F.; Holst, Jens J.; Vilsbøll, Tina; Knop, Filip K.
Abstract : Aims: The duodenal‐jejunal bypass sleeve ((DJBS) or EndoBarrier Gastrointestinal Liner) induces weight loss in obese subjects and may improve glucose homeostasis in patients with type 2 diabetes (T2D). To explore the underlying mechanisms, we evaluated postprandial physiology including glucose metabolism, gut hormone secretion, gallbladder emptying, appetite and food intake in patients undergoing DJBS treatment. Material and methods: A total of 10 normal glucose‐tolerant (NGT) obese subjects and 9 age‐, body weight‐ and body mass index‐matched metformin‐treated T2D patients underwent a liquid mixed meal test and a subsequent ad libitum meal test before implantation with DJBS and 1 week (1w) and 26 weeks (26w) after implantation. Results: At 26w, both groups had achieved a weight loss of 6 to 7 kg. Postprandial glucagon‐like peptide‐1 (GLP‐1) and peptide YY responses increased at 1w and 26w, but only in T2D subjects. In contrast, glucose‐dependent insulinotropic polypeptide responses were reduced only by DJBS in the NGT group. Postprandial glucose, insulin, C‐peptide, glucagon, cholecystokinin and gastrin responses were unaffected by DJBS in both groups. Satiety and fullness sensations were stronger and food intake was reduced at 1w in NGT subjects; no changes in appetite measures or food intake were observed in the T2D group. No effect of DJBS on postprandial gallbladder emptying was observed, and gastric emptying was not delayed. Conclusions: DJBS‐induced weight loss was associated with only marginal changes in postprandial physiology, which may explain the absence of effect on postprandial glucose metabolism.